Exercise and Parkinson's: benefits for cognition and quality of life - Cruise, K.; Bucks, R.; Loftus, Andrea; Newton, R.; Pegoraro, R.; Thomas, M. (Wiley-Blackwell Publishing, Inc., 2011)
Objectives – The benefits of physical exercise for psychological aspects of quality of life (QoL) are well established in normally ageing adults, yet potential benefits for people with Parkinsons disease (PD)have received limited attention. This study evaluated the benefits of exercise for cognitive functioning, mood and disease-specific QoL for people with PD. Methods – Twenty-eight individuals with PD wereallocated to an exercise intervention program (EIP, n = 15) or control group (n = 13). The EIP group undertook a programme of progressive anabolic and aerobic exercise twice weekly for 12 weeks. The control group maintained their usual lifestyle. Results – Exercise was shown to have selective benefits for cognitive functioning by improving frontal lobe based executive function. No significant effects were demonstrated for mood or disease-specific QoL. Conclusions – These results are consistent with previous research demonstrating selective benefits of exercise for executive function among normal ageing adults and PD.